2012
DOI: 10.1177/1866802x1200400202
|View full text |Cite
|
Sign up to set email alerts
|

I Want It All, and I Want It Now: The Political Manipulation of Argentina's Provincial High Courts

Abstract: Provincial supreme courts are important players in local politics because justices can affect the interest of the ruling governors; however, no research has addressed the factors that affect judicial turnover in provincial high courts in new democracies. This research attempts to fill this gap by using original data on the 525 departures of all provincial high court justices in Argentina from 1983 to 2009. My guiding hypothesis is that the stability of a justice on the bench depends on the political proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
1
0
21
Order By: Relevance
“…Instead they became important sources of votes and other forms of political support for national political elites. According to experts, these subnational undemocratic regimes (SURs) have been resilient because of a number of factors, including, among others, the exclusionary practices of elites, such as the distortion of local electoral rules and procedures (Behrend and Whitehead 2016;Benton 2012;Calvo and Micozzi 2005), the stacking of electoral commissions with political allies (Rebolledo 2011), the politicization of local judiciaries (Brinks 2007;Castagnola 2012;Chavez 2004;Leiras, Tuñón, and Giraudy 2015), and the perpetration of extra-legal violence against opposition (Gibson 2005a). Other studies have demonstrated that economic factors explain the emergence and durability of subnational authoritarianism, including local political economies (Behrend 2011;Hale 2003;McMann 2006), inter-governmental fiscal transfers (Diaz-Rioseco 2016; Gervasoni 2010b), and subnational undemocratic regimes insertion into global markets (Libman and Obydenkova 2014).…”
Section: Democracy and Welfare State Universalism: Concepts And Measuresmentioning
confidence: 99%
“…Instead they became important sources of votes and other forms of political support for national political elites. According to experts, these subnational undemocratic regimes (SURs) have been resilient because of a number of factors, including, among others, the exclusionary practices of elites, such as the distortion of local electoral rules and procedures (Behrend and Whitehead 2016;Benton 2012;Calvo and Micozzi 2005), the stacking of electoral commissions with political allies (Rebolledo 2011), the politicization of local judiciaries (Brinks 2007;Castagnola 2012;Chavez 2004;Leiras, Tuñón, and Giraudy 2015), and the perpetration of extra-legal violence against opposition (Gibson 2005a). Other studies have demonstrated that economic factors explain the emergence and durability of subnational authoritarianism, including local political economies (Behrend 2011;Hale 2003;McMann 2006), inter-governmental fiscal transfers (Diaz-Rioseco 2016; Gervasoni 2010b), and subnational undemocratic regimes insertion into global markets (Libman and Obydenkova 2014).…”
Section: Democracy and Welfare State Universalism: Concepts And Measuresmentioning
confidence: 99%
“…Las Cortes judiciales son actores centrales en la política nacional y subnacional (Ward 2003;Bill Chavez 2004;Hilbink 2007;Whittington 2007;Smulovitz 2010;Castagnola 2012;Ingram 2012 Llanos, Tibi Weber, Heyl, y Stroh 2016). Las Cortes pueden frenar un proyecto o una política pública del gobierno, y según los casos inciden también en conflictos partidarios y electorales.…”
Section: Marco Teórico Propuesta Y Argumentounclassified
“…En Argentina existe una rotación frecuente de jueces en los STJ provinciales y la literatura señala que los incentivos partidarios son un gran predictor de esos cambios en las Cortes (Castagnola 2010a(Castagnola , 2012Leiras, Giraudy y Tuñón 2015). Sin embargo, no existe una clara relación entre estos cambios y el poder partidario de que disponen los gobernadores (Castagnola 2010a(Castagnola , 2012Leiras, Giraudy y Tuñón 2015).…”
Section: Marco Teórico Propuesta Y Argumentounclassified
See 2 more Smart Citations